Oral health of children with acute lymphoblastic leukemia: A review - Kadalagere Lakshmana Girish Babu; Joe Mathew; Geeta Maruti Doddamani; Jagadish Kyatsandra Narasimhaiah; Lambani Ramanaik Kumarswamy Naik (Wolters Kluwer Medknow Publications, 2016)
Leukemia is a malignancy of the bone marrow and blood. It is the most common childhood cancer in India. Advances in the treatment regimens have greatly increased the chances of survival. Both the disease and its treatment change the oral environment. In some cases, oral manifestations are the presenting feature of the disease and it will be the dentist's responsibility to identify the underlying disorder and guide the diagnosis of the patient. Hence, the aim of present article is to review the literature concerning the oral health of children with acute lymphoblastic leukemia (ALL).